Learning Mathematics "Asyik" with Youtube Educative Media. Issue 2 (March 2020) - Sari, W N; Samosir, B S; Sahara, N; Agustina, L; Anita, Y
Abstract: The research aims to find out how the use of YouTube Educative as education media by students, parents, and teachers in improving knowledge, skills, and creativity generally in education and especially in mathematics studies. Besides that research also recommend YouTube Educative to help students so that learning mathematics becomes fun. This study applied descriptive qualitative research.This study applied descriptive qualitative research. The subjects of this study were the principal (headmaster), students and mathematics teachers. The object of this research was YouTube. The results of the study found that principal (headmaster), teachers, and students had not taken the advantages of YouTube as educative media in mathematics learning activities. Youtube is mostly used for playing games, watching cartoons, funny videos, arts and cooking recipes. Recommendation related to the use of YouTube Educative help students more easily understand concepts and learn mathematics becomes more fun.